Cooperative Carbon Dioxide Adsorption in Alcoholamine‐ and Alkoxyalkylamine‐Functionalized Metal–Organic Frameworks. Issue 44 (4th February 2020) - Mao, Victor Y.; Milner, Phillip J.; Lee, Jung‐Hoon; Forse, Alexander C.; Kim, Eugene J.; Siegelman, Rebecca L.; McGuirk, C. Michael; Zasada, Leo B.; Neaton, Jeffrey B.; Reimer, Jeffrey A.; Long, Jeffrey R.
Abstract: A series of structurally diverse alcoholamine‐ and alkoxyalkylamine‐functionalized variants of the metal–organic framework Mg2 (dobpdc) are shown to adsorb CO2 selectively via cooperative chain‐forming mechanisms. Solid‐state NMR spectra and optimized structures obtained from van der Waals‐corrected density functional theory calculations indicate that the adsorption profiles can be attributed to the formation of carbamic acid or ammonium carbamate chains that are stabilized by hydrogen bonding interactions within the framework pores. These findings significantly expand the scope of chemical functionalities that can be utilized to design cooperative CO2 adsorbents, providing further means of optimizing these powerful materials for energy‐efficient CO2 separations. Abstract : Cooperative CO2 chemisorption is achieved in a metal–organic framework functionalized with structurally diverse alcoholamines and alkoxyalkylamines. Solid‐state NMR spectroscopy and DFT calculations indicate that CO2 adsorption occurs via the formation and propagation of hydrogen bond‐stabilized carbamic acid or ammonium carbamate structures.